Multipurpose Card Using Rfid Technology (International Journal of Engineering and Computer Science, 2017)
Most often in our daily life we have to carry lot of  cards such as credit cards, debit cards and some other special cards for toll system ERP, parking and personal identification purpose. Currently smart card implementations can be seen around the world but they are not unified i.e. each developers uses different programming standards and data structures. The smart card will provide service to the user only within a university campus or an organization.In order to make available such multiple application access using a single card to every individual person we have planned to use RFID technology, which is cost effective. As RFID technology is used in the proposed concept, the programming standards and data structures will be unified. Unlike smart card, the RFID card can be used by every individual person to access different applications. Thus, a person needs not to carry number of cards; he can just carry a single card for different purpose.